Effectiveness of physical therapy in addition to occlusal splint in myogenic temporomandibular disorders: protocol of a randomised controlled trial - Cristina Incorvati; Antonio Romeo; Adele Fabrizi; Luca Defila; Carla Vanti; Maria Rosaria Antonella Gatto; Claudio Marchetti; Paolo Pillastrini (BMJ Open)
Introduction Temporomandibular disorders (TMDs) are considered a collection of musculoskeletal conditions involving the masticatory muscles, the temporomandibular joint and associated structures. The myogenous group appears to represent the most frequently diagnosed category. In the context of a multimodal approach, splint therapy and musculoskeletal physiotherapy are often considered as a preferred therapy. The purpose of this study will be to investigate the effects of musculoskeletal physiotherapy combined with occlusal splint and education versus occlusal splint and education alone in the treatment of chronic myogenous TMD on pain and mandibular range of motion.Methods and analysis All consecutive adults complaining of TMDs presented to the Department of Biomedical and Neuromotor Sciences of the University of Bologna will be considered eligible. Inclusion criteria shall be based on the presence of myogenous TMDs, as diagnosed through clinical examination in reference to the international diagnostic criteria of TMDs. Randomisation, concealed allocation, blinded assessment and intention-to-treat analysis will be employed. The splint therapy will consist of the use of the splint every night and concurrent delivery of an educational programme; the protocol shall have a duration of three consecutive months. The combined musculoskeletal physiotherapy, splint therapy and education will additionally consist of manual therapy techniques and exercise; such protocol shall consist of a duration of three consecutive months, inclusive of 10 sessions for the enhanced elements. All outcome measures will be collected at baseline, after treatment and at a 6 months follow-up.Ethics and dissemination Ethical approval has been obtained from the Independent Ethic Committee in Clinical Research of AUSL Bologna-Italy (47/2018/SPER/AUSLBO). Pursuant to applicable rules,we will obtain informed consent from each participant and collect data anonymously to maintain privacy. Results will be disseminated to clinicians and researchers through peer-reviewed publications and conferences.Trial registration number NCT03726060